European Bison as a Refugee Species? Evidence from Isotopic Data on Early Holocene Bison and Other Large Herbivores in Northern Europe - Bocherens, Hervé (PLoS One, 2015)
According to the refugee species concept, increasing replacement of open steppe by forest cover after the last glacial period and human pressure had together forced European bison (Bison bonasus)—the largest extant terrestrial mammal of Europe—into forests as a refuge habitat. The consequent decreased fitness and population density led to the gradual extinction of the species. Understanding the pre-refugee ecology of the species may help its conservation management and ensure its long time survival. In view of this, we investigated the abundance of stable isotopes (δ(13)C and δ(15)N) in radiocarbon dated skeletal remains of European bison and other large herbivores—aurochs (Bos primigenius), moose (Alces alces), and reindeer (Rangifer tarandus)—from the Early Holocene of northern Europe to reconstruct their dietary habits and pattern of habitat use in conditions of low human influence. Carbon and nitrogen isotopic compositions in collagen of the ungulate species in northern central Europe during the Early Holocene showed significant differences in the habitat use and the diet of these herbivores. The values of the δ(13)C and δ(15)N isotopes reflected the use of open habitats by bison, with their diet intermediate between that of aurochs (grazer) and of moose (browser). Our results show that, despite the partial overlap in carbon and nitrogen isotopic values of some species, Early Holocene large ungulates avoided competition by selection of different habitats or different food sources within similar environments. Although Early Holocene bison and Late Pleistocene steppe bison utilized open habitats, their diets were significantly different, as reflected by their δ(15)N values. Additional isotopic analyses show that modern populations of European bison utilize much more forested habitats than Early Holocene bison, which supports the refugee status of the species.